(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
One of the urgent problems of the oil industry is to improve the efficiency of well operation. It is of particular relevance in the development of anomalous (non-Newtonian) oil deposits, where the operation of wells is complicated by the manifestation of anomalies in the viscosity and mobility of oil, the formation of asphalt-resin-paraffin deposits (ARPD) and high-viscosity emulsions in the bottomhole zone of the reservoir (UPZ).